Crafting theory to satisfy the requirements of systems science. Issue 4 (December 2016) - Demetis, Dionysios S.; Lee, Allen S.
Abstract: Just as Lee, Briggs, and Dennis (2014) showed that a rigorous conception of "explanation" leads to requirements for a positivist theory to satisfy, and just as Lee and Hovorka (2015) showed that a rigorous conception of "interpretation" leads to requirements for an interpretive theory to satisfy, we show that a rigorous conception of "systems" leads to certain requirements for a systems theory to satisfy. We apply basics of systems science in general, as well as basics of Luhmann's (Luhmann, 1995; Moeller, 2006) systems perspective in particular. We illustrate these basics with empirical material from a case about the role of information technology in anti-money laundering. The example demonstrates that research in information systems, which has been informed by positivism, interpretivism, and design, can be additionally and beneficially informed by systems science — which, ironically, has been largely absent in information "systems" research. Highlights: Re-introduces the rightful place of systems theory in IS research A set of six main requirements to satisfy systems sciences is proposed. General Systems Theory (GST) is integrated with Niklas Luhmann's systems theory.